Asan, The Traditional Market of Kathmandu Valley: Analyzing Market Trend and Consumer Buying Behavior of Such Market - Sharma, Shivani; Sahani, Suresh Kumar; Chaudhary, Bhawesh; Sahani, Kameshwar; Sah, Narayan (Lembaga Yasin AlSys, 2023)
Asan is a hub for business in the Kathmandu valley famed for its bazaar, festive calendar, and historic location. This research looks at how the market is changing and how people shop in Asan, which is a blend of old and new ways of doing things. Apart from that, it is also one the most popular trade route for India-Tibet that passes through Kathmandu. To get in-depth knowledge about this old but traditional marketplace for this research paper I have chosen various approaches such as interviews, past data analysis, and surveys. On that basis, i saw how the market is changing over time, influenced by global trends and new business methods. This research is all about studying how people in Asan shop. I look at all the different things like culture, history, and how much money people have that affect how they decide what to buy. Our findings show how tradition, community, and modern ways of doing things impact what people choose to purchase in this market. This research helps us learn more about why Asan is important as an old-style market. It also helps us understand how other traditional markets around the world might work in our modern, globalized world. What we've learned can be useful for people who run markets, government leaders, and business owners who want to keep and make these cultural places even better.